Amended Agreements of medical liability Comparative study between UAE and English law - زين ايمن محمد (Journal of Legal Sciences, 2018)
The study attempts to focus on the organized agreements of medical liability, after frequent use experience of these agreements, which come often either exempt civil liability or limit, which making the Researcher to submit the study to the light of the laws of the UAE and the law of English, to be collected in the final recommendations to guide the Legislature of UAE according to the Law of Medical Responsibility 2016. The search consist of two main themes, dealt in the first section with the application of the terms of the exemption or limitation of responsibility in the general rules, and comparing with the agreements of Medical Responsibility, the second section focused on items that emphasize Medical Responsibility, because it involves the study of approach between the rules of the exemption or limitation of Medical Responsibility and conditions of Compliance Contracts. The Researcher end to a number of conclusions and recommendations, in a doctrinal try, purposed to shed light on an important legal aspect, in the framework of the relationship between the Patient and the Doctor.